RANCIÈRE, Jacques. O espectador emancipado. 1ª edição. Trad. Ivone C. Benedetti. São Paulo: WMF Martins Fontes, 2012 - Cunha, Valdeci da Silva (História e Diversidade, 2016)
Resenha do livro: RANCIÈRE, Jacques. O espectador emancipado. 1ª edição. Trad. Ivone C. Benedetti. São Paulo: WMF Martins Fontes, 2012.